Pivoting Away From Oil: A Sector Analysis of Nigeria’s Economy Aimed at Achieving Diversification and Inclusive Growth - Ojei, Onyeka (Université d'Ottawa | University of Ottawa, 2017)
Nigeria, currently the largest economy in Africa, is a lower-middle-income mixed economy that had been experiencing strong economic growth averaging 5% for over ten years and was on course to becoming a global economic powerhouse. However, as a direct result of its over-reliance on the oil industry, the economy fell into a major recession in 2016. The oil industry represents just 10% of Nigeria’s economy, but more than 70% of the country’s revenue and about 90% of its foreign exchange comes from the same sector. Thus, the global oil price plunge experienced in 2016 along with a fall in Nigeria’s oil supply catapulted the economy into an economic crisis and revealed the country’s economic vulnerability and the consequences of its oil dependency. This paper seeks to understand why the other 90% of the economy (the non-oil economy) produces so little value, by analyzing the Agricultural, Manufacturing and Services sectors. It examines the urban and rural divide in each sector and identifies each sectors constraint to productivity that when addressed, could lead to a full and inclusive economic growth.